Hubungan Rasionalitas Penggunaan Antibiotik Terhadap Outcome Klinik Pasien Pneumonia Komunitas Rawat Inap di RSUD. Dr. H. Abdul Moeloek Provinsi Lampung Tahun 2019 - Widiyastuti, Asih; Kumala, Shirly; Utami R, Hesty; Pratama, Anton (Jurnal Kesehatan, 2023)
Pneumonia is a lung parenchyma disease caused by bacteria, fungi, viruses, and parasites. Irrational use of antibiotics will lead to antibiotic resistance, so the goal of therapy has yet to be achieved. This study evaluates the rationality of using community antibiotics for the clinical outcome of community pneumonia patients in RSUD. Dr. H. Abdul Moeloek.This research is descriptive-analytic with a cross-sectional design and retrospective data retrieval from medical records in 2019. The data analysis was carried out descriptively, and the correlation analysis of the rationale of antibiotic use with clinical outcomes using the Spearman test. The study's results of 144 analyzed showed the characteristics of community pneumonia patients, 78 male, and 66 female patients. The evaluation of the use of antibiotics using the ATC/DDD method showed that Ceftriaxon DDD was 46.80 DDD/100 patient-days, Azithromycin (23.91 DDD/100 patient-days), Levofloxacin (22.70 DDD/100 patient-days). With the Gyssen method, patients used antibiotics correctly (category 0) by 72.91% and incorrectly (categories I – VI) by 27.09%. Statistical analysis showed a significant relationship (p-value=0.003) between the rational use of antibiotics and patient clinical outcomes. Further research is needed regarding the incidence of Drugs Related Problems on the clinical effects of community pneumonia patients.